Quantum-disordered state of magnetic and electric dipoles in an organic Mott system. Issue 1 (December 2017) - Shimozawa, M.; Hashimoto, K.; Ueda, A.; Suzuki, Y.; Sugii, K.; Yamada, S.; Imai, Y.; Kobayashi, R.; Itoh, K.; Iguchi, S.; Naka, M.; Ishihara, S.; et al.
Abstract Strongly enhanced quantum fluctuations often lead to a rich variety of quantum-disordered states. Developing approaches to enhance quantum fluctuations may open paths to realize even more fascinating quantum states. Here, we demonstrate that a coupling of localized spins with the zero-point motion of hydrogen atoms, that is, proton fluctuations in a hydrogen-bonded organic Mott insulator provides a different class of quantum spin liquids (QSLs). We find that divergent dielectric behavior associated with the approach to hydrogen-bond order is suppressed by the quantum proton fluctuations, resulting in a quantum paraelectric (QPE) state. Furthermore, our thermal-transport measurements reveal that a QSL state with gapless spin excitations rapidly emerges upon entering the QPE state. These findings indicate that the quantum proton fluctuations give rise to a QSL—a quantum-disordered state of magnetic and electric dipoles—through the coupling between the electron and proton degrees of freedom. The organic materialκ -H3 (Cat-EDT-TTF)2 has been suggested to exhibit a quantum spin liquid phase in which quantum fluctuations prevent the formation of magnetic order. Here, the authors show that this may be a result of fluctuations of hydrogen atoms, rather than more conventional geometric frustration.